PENTINGNYA PENGGUNAAN PROGRAM APLIKASI INSTRUMENTASI DATA UNTUK MENGGALI ARAH PEMINATAN PESERTA DIDIK SMP DI KABUPATEN PAMEKASAN - Agus Supriadi (LP2M IAI Al Khairat Pamekasan, 2021)
With so many tasks that must be completed cultivated fields by teachers Guidance and Counseling which consists of four fields, eleven types of services, and six support units. The teacher then Guidance and Counseling feel overwhelmed and unable to complete the task becomes all areas mandate, particularly in data collection and usage instrumentation applications. Unfinished inability to complete all the administrative tasks of the Guidance and Counseling teacher, now coupled with new task field known as Direction Specialisation, which according to teachers Guidance and Counseling